PENDAMPINGAN TEKNIS APLIKASI BAHAN ORGANIK EKSOGEN PADA LAHAN HORTIKULTURA KELOMPOK TANI MEKAR BARU DI DESA WAIMITAL KABUPATEN SERAM BAGIAN BARAT - Kesaulya, Henry; Laisina, Jane J.K.; Hehahanussa, Meitty L.; Matatula, Ervina A.; Devinubun, Fatima; Patrouw, Jopy (Universitas Pattimura, 2024)
Providing exogenous organic materials is a very important ingredient in efforts to safely improve soil productivity, so that the resulting products are safe for consumption and free from chemical contamination. The application of organic fertilizer to horticultural land will directly affect crop yields. The aim of community service on horticultural land in the Mekar Baru farmer group in Waimital village is as an effort to assist and strengthen the plant cultivation system for farmers in maintaining land productivity and sustainable production based on the application of organic fertilizer. The method used is technical assistance to farmers during plant cultivation. The results of the technical assistance provided show that new awareness has been built in the horticultural plant cultivation system. This indicator shows that the application of liquid organic fertilizer to several horticultural plants on farmers' land is better than on land that does not receive organic fertilizer.